Systematic review with qualitative meta-synthesis of parents’ experiences and needs in relation to having a child or young person with a mental health difficulty - Dania Dahmash; Andrea Anastassiou; Sarah Glover; Sarah Halligan; Faith Martin; Charlie Duncan; Sarah Wicker; Lucy Docherty (BMJ Mental Health)
Question What are the experiences and needs of parents of children and young people (CYP) aged 5–18 with diagnosed mental health difficulties, particularly in relation to the parents’ own well-being?Study selection and analysis A systematic review with thematic meta-synthesis was conducted, including qualitative studies published in English. Seven databases were searched (MEDLINE, PsycINFO, CINAHL Ultimate, AMED, EMBASE, Web of Science and Cochrane Library) from inception to September 2024. Studies focused on parents of CYP aged 5–18 years, where the CYP had a confirmed mental health diagnosis.Findings Of 75 862 screened studies, 46 met inclusion criteria. Six overarching themes were identified: support needs and gaps; impact on everyday life; altered family dynamics; parental worries and fears; emotional experience of caregivers and self-care paradox. Parents face significant challenges, including unmet support needs from healthcare and education systems, substantial impacts on daily life and altered family dynamics. Emotional experiences such as worry, guilt and stigma were pervasive, compounded by systemic gaps in information and resources. Parents often prioritise their child’s needs over their own, creating barriers to self-care. These challenges were consistent across diagnoses but heightened in cases of life-threatening conditions like eating disorders and depression.Conclusions The findings highlight support needs for parents of CYP with mental health difficulties. Tailored interventions, better professional training and family centred care are needed. Future research should focus on developing theoretical models of parental distress to guide interventions and inform support mechanisms that mitigate these broad impacts on parents’ well-being.